2021
DOI: 10.3389/fcell.2021.719636
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Modulation of Neurite Outgrowth in Human Neural Progenitor Cells by Inhibiting Non-muscle Myosin II

Abstract: Studies on neural development and neuronal regeneration after injury are mainly based on animal models. The establishment of pluripotent stem cell (PSC) technology, however, opened new perspectives for better understanding these processes in human models by providing unlimited cell source for hard-to-obtain human tissues. Here, we aimed at identifying the molecular factors that confine and modulate an early step of neural regeneration, the formation of neurites in human neural progenitor cells (NPCs). Enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 67 publications
1
10
0
Order By: Relevance
“…Total neurite outgrowth at different time points was determined on the basis of green fluorescence and morphological parameters, whereas the corresponding cell numbers of GFP-NPCs were quantified based on the nuclear staining (Figure 2A). We found that untreated GFP-NPCs 48 h after plating gradually develop protrusions at a rate of 7.09 ± 2.03 mm/cell/48 h (~80% increase within the following 48 h), which is consistent with our previous findings on neurite growth rate of unstimulated GFP-NPCs grown on pOrn/Lam coated surface (Lilienberg et al, 2021). NPCs under the applied conditions exhibit a moderate proliferation rate (cell number increased by ~20% per day, the equivalent of a doubling time of 4 days).…”
Section: Effect Of Naïve Microglia On Human Neural Progenitor Cellssupporting
confidence: 92%
See 4 more Smart Citations
“…Total neurite outgrowth at different time points was determined on the basis of green fluorescence and morphological parameters, whereas the corresponding cell numbers of GFP-NPCs were quantified based on the nuclear staining (Figure 2A). We found that untreated GFP-NPCs 48 h after plating gradually develop protrusions at a rate of 7.09 ± 2.03 mm/cell/48 h (~80% increase within the following 48 h), which is consistent with our previous findings on neurite growth rate of unstimulated GFP-NPCs grown on pOrn/Lam coated surface (Lilienberg et al, 2021). NPCs under the applied conditions exhibit a moderate proliferation rate (cell number increased by ~20% per day, the equivalent of a doubling time of 4 days).…”
Section: Effect Of Naïve Microglia On Human Neural Progenitor Cellssupporting
confidence: 92%
“…The neural progenitor cell lines used in this study have previously been generated and characterized in detail ( Yu et al, 2014 ; Vofely et al, 2018 ; Lilienberg et al, 2021 ). These cells express no pluripotency markers, such as Nanog and Oct4; but the typical neural progenitor markers, such as Nestin and SOX2; as well as the neuronal markers, such as NeuroD1, FOXG1, and PAX6 ( Yu et al, 2014 ; Vofely et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations